(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The aim of this research is to define the role of the school climate in enhancing social cohesion from the point of view of teachers in secondary schools in Latakia Governorate, And the effect of variables (type of school, location of the school, branch of study) on that, In order to achieve the research objectives, the descriptive approach was used by designing a questionnaire that consisted of three dimensions: (social affiliation, social integration, and social loyalty), It was distributed on a sample consisting of (416) male and female teachers in secondary schools in Latakia Governorate, and among the most important results of the research were: • The role of the school climate in promoting social belonging came with a moderate degree from the viewpoint of teachers in secondary schools in Latakia governorate. • The role of the school climate in promoting social inclusion came with a moderate degree from the viewpoint of teachers in secondary schools in Latakia governorate. • The role of the school climate in enhancing social loyalty from the viewpoint of teachers in secondary schools in Latakia Governorate came to a high degree. • There were no statistically significant differences between the mean scores of the responses of the research sample regarding the role of the school climate in enhancing social cohesion according to the school type variable (male, female, mixed). • The presence of statistically significant differences between the mean scores of the responses of the research sample regarding the role of the school climate in enhancing social cohesion according to the school location variable (city, countryside), in favor of city schools. • The presence of statistically significant differences between the mean scores of the responses of the research sample regarding the role of the school climate in promoting social cohesion according to the variable of the study branch (scientific, literary), in favor of the literary branch, except for the dimension (social loyalty).